Belgian Freemasonry and the Colonial Project in the Congo (1876-1914). (17th December 2015) - Maes, Anaïs
Abstract : Although the history of Belgian colonization of the Congo is predominantly associated with the hegemony of the Catholic Church over the territory, first in the Congo Free State, later in the Belgian Congo, Belgian freemasonry was not uninterested in the colonial projects of King Leopold II and in the subsequent take-over by the Belgian state. However, before 1914, the interaction between freemasonry and the colonial history of Congo would prove relatively brief and rather limited. It would mainly show how far the metropolitan political struggles of a liberal, secular and anticlerical freemasonry were extended to the country's colonial territory. In contrast to colonial settings other than the Belgian one, the Congolese lodges were far from numerous and had a very limited membership. That same membership was more international than average, but remained quite Belgian nevertheless. The endeavour to introduce lodges into the colonial territory had a distinct Belgian nationalist ring to it, as it was clearly related to a determination not to let foreign grand lodges best the Grand Orient de Belgique in a kind of masonic 'Scramble for Africa'.